Chartered accountancy and resistance in South Africa - Terblanche, J.; Waghid, Y. (South African Journal of Higher Education, 2021)
In recent times, the chartered accountant profession was regularly in the news for reasons pertaining to the unethical and unprofessional behaviour of members. The profession has an important role to play in the South African economy, as members will often fulfil important decision-making roles in business. In a response to the dilemmas the profession is facing, we analysed the implications for the profession and society due to a resistance to include research as a pedagogical activity in the chartered accountancy educational landscape. Through deliberative research activities, students have the opportunity to engage with community members and with societal challenges that could foster reflexivity and humaneness in students. In addition, critical and problem-solving skills are cultivated. These are skills that are difficult to assess in the form of an examination, and the absence of research as pedagogical activity in this particular educational landscape, impacts the cultivation of these skills in future chartered accountants. This is so, as the chartered accountancy educational landscape is significantly influenced by the power that resonates within the profession and culminates into the disciplinary power mechanism of the examination. The South African Institute of Chartered Accountants (SAICA) set an external examination, called the Initial test of Competence (ITC), which graduates need to write upon leaving institutes of higher learning. Success in this SAICA-examination therefore impacts on the teaching and learning pedagogy adopted by chartered accountants in academe. If chartered accounting students were instead primarily being exposed to technical content assessed via an examination, also being exposed and introduced to deliberative research, the possibility exists that students, through critical reflexivity, could move beyond the constraints of the self to that of the communal other in line with the African notion of ubuntu can be enhanced.